Moderating role of Digital Consumer Protection in Impacting the Intention to Use Digital Financial Services - Singh, Pushpkiran; Dave, Tejas; Joshi, Ashish B. (International Review of Management and Marketing, 2024)
Digital finance has the potential to increase financial services accessibility and financial inclusion of the people in need. Digital Financial Services encompass a range of financial services that are accessible and utilized via digital platforms, including lending, payments, insurance, and eventually personal finance management. In addition to more contemporary financial solutions like digital lending platforms, crowdfunding platforms, peer-to-peer (P2P) lending, digital payments, e-commerce, mobile wallets, and app-based lending, digital financial services also include more traditional financial solutions like credit and debit cards, and point of sale (PoS) systems. The moderating role of digital consumer protection in impacting the association between the five variables usability of services, facilitating conditions of the consumers, usage experience, trust and technology self-efficacy of the customers and the consumers’ intention to use digital financial services has been investigated in this research. Data has been collected from 528 people of Gujarat, India, belonging to the middle- and higher-income groups through random sampling technique. A structured equation modelling approach has been adapted and the test of the model developed makes it clear that digital consumer protection moderates the relationship between technology self-efficacy of consumers and their intention to use digital financial services. Similarly, it also moderates the relationship between the usability of financial services and intention to use digital financial services. However, it does not moderate relationship between facilitating conditions, usage experience, trust and consumers’ intention to use digital financial services.